Sophie's Lovely Locks - Villnave, Erica Pelton (Tarrytown, NY : Marshall Cavendish Children, 2011)
Sophie loves her long hair, but when it becomes too hard to manage and she decides to get it cut, she finds something generous to do with it.
Keywords: Hair -- Fiction